Science as a Mythologized Phenomenon - K. Gizatova, Gulnaz; G. Ivanova, Olga; R. Karimov, Artur; N. Stepanenko, German; A. Tereshchenko, Natalya; M. Shatunova, Tatyana (International Journal of Psychosocial Rehabilitation, 2020)
It is commonly believed that the scientific discourse is free from mythological stratification and that this freedom is provided by the profound theoretical nature of strict rationality. However, the practice of sociohumanitarian research gives reason to believe that scientific discourse also has a narrative character. The main idea of this article is to identify the limits for the scientific theory possibilities and to discover ways to mythologize scientific discourse. This is important, since the abolition of purely rationalistic approaches leads to the appearance of a "blind spot," which does not allow us to see and analyze new trends in real life. During the study, the methods of classical and negative dialectics were used, as well as the principle of deconstruction, developed in the framework of postmodern discourse and beyond its borders. These approaches are combined in the logic of coincidenceology, which makes it possible to combine previously incompatible methodologies. As a result of the analysis, it was revealed that the scientific discourse can be subject to mythologization/ideologization, and claims for the ability to demythologize large narratives by “scientification” are illusory. Moreover, the scientific theory itself can be adequate to its subject only when it goes beyond its boundaries, capturing marginal areas of knowledge, including the metaphysical component.